2021
DOI: 10.1002/ceat.202000619
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study of the Impact of Initial Turbulence on the Explosion Behavior of Methane‐Air Mixtures

Abstract: The experimental parameters that significantly affect the gas explosion process were determined, investigating the pressure, temperature, and velocity in the methane‐air explosion process under quiescent and turbulent conditions. Experiments and computational fluid dynamics simulations were integrated to optimize the experimental parameters and elucidate the impact of the initial turbulence on the explosion behavior of methane‐air mixtures. Good agreement was achieved between the computed results and experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…The findings of this study confirm the argument that intensifying flame folding and turbulence in the T-shaped pipe branches leads to an increase in explosion pressure. The study by Wang Hua et al [20] examined the impact of initial turbulence on methane-air explosions. According to the experimental results, initial turbulence contributes to an increase in both the maximum explosion pressure and the maximum rate of pressure rise.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of this study confirm the argument that intensifying flame folding and turbulence in the T-shaped pipe branches leads to an increase in explosion pressure. The study by Wang Hua et al [20] examined the impact of initial turbulence on methane-air explosions. According to the experimental results, initial turbulence contributes to an increase in both the maximum explosion pressure and the maximum rate of pressure rise.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the explosion characteristics of CH 4 /air will change with an increase of the initial temperature. Wang and Chen 13 studied the pressure, temperature, and velocity of CH 4 /air explosion in turbulent conditions by using electric spark ignition to induce CH 4 /air explosion. It was found that the initial turbulence can increase the maximum explosion pressure and maximum pressure rise rate, shorten the time to reach the maximum explosion pressure, and improve the explosion intensity and destructive force of CH 4 /air.…”
Section: Introductionmentioning
confidence: 99%